Adsorption and protonation of peptides and proteins in pH responsive gels - Longo, Gabriel S; Szleifer, Igal (Journal of physics. D, Applied physics, 2016)
To describe the non-trivial features of the equilibrium protonation and physical adsorption of peptides/proteins in pH-responsive hydrogels, we summarize our recent theoretical work on the subject. In these systems, molecular confinement in nanometer-sized environments modifies the balance between chemical state, physical interactions and molecular organization, which results in a behavior that is qualitatively different from what is expected from assuming the bulk solution protonation. To enhance adsorption, the pH-dependent deprotonation curves of all amino acids of adsorbed proteins are adequately shifted and deformed, which depends, in a complex fashion, on the specific amino acid. This possibility of modifying different acid-base equilibriums gives the adsorbed protein degrees of freedom to regulate charge and enhance electrostatic attractions under a wide range of experimental conditions. Protein adsorption modifies the microenvironment inside the hydrogel, particularly the gel pH. As a result, the state of protonation of the network is different before and after adsorption. The physicochemical considerations described in this review can be useful in the design of functional materials involving protein adsorption.